Analisis Faktor-faktor Hambatan dan Persepsi Konsumen terhadap Penerapan Reverse Logistic Menggunakan Metode HRL (House of Reverse Logistic ) di Perusahaan Ban - Armadani, Aditya Cahya; Pulansari, Farida (Ekonomis: Journal of Economics and Business, 2025)
This study aims to propose a maturity framework design in reverse logistics implementation and design a house of reverse logistics (HRL) to understand customer needs and desires regarding the implementation of reverse logistics (RL). This study uses the quality function deployment (QFD) method. The data source used in this study is the results of a questionnaire. The questionnaire was collected, statistical tests were conducted to test the adequacy of the data, validity, and reliability. The objects of this study were rubber (tire) companies PT XYZ; PT ABC; and PT EFG, while PT XYZ was the subject in this study. The results of the analysis found that the maturity level of reverse logistics implementation in these three tire companies was categorized as level 2 (Level managed). The House of Reverse Logistic design that has been created shows that consumer satisfaction and expectations regarding the implementation of this RL are quite good.